PERANAN CELPeranan Celebrity Endorser dan Brand Awareness terhadap Keputusan Pembelian Konsumen Jogja Cushy CheeseEBRITY ENDORSER DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN JOGJA CUSHY CHEESE - Mu'tashim Billah Murtadlo; Yunisa Azizah (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2019)
Today's business world is being led to be able to create product advertisements more creatively and innovatively, this makes celebrities an interesting spotlight to be able to introduce these products. Introducing products to the community will make people aware of the existence of these brands, and can be an alternative for people in choosing similar products. Celebrity endorser and Brand Awareness are part of the factors that influence Consumer Purchasing Decisions. The purpose of this study was to determine the effect of Celebrity Endorser and Brand Awareness on the Jogja Cushy Cheese Consumer Purchase Decision process. This research is a quantitative study using correlation analysis and multiple linear regression analysis, data collected by questioner from 100 respondents.. The results obtained that Celebrity Endorser and Brand Awareness have a significant and partial effect simultaneously on consumer purchasing decisions. And the most influential variable on consumer purchasing decisions is variable brand awareness.